Prognostic value of O-6-methylguanine-DNA methyltransferase loss in salivary gland carcinomas - Scesnaite, Asta; Jarmalaite, Sonata; Müller, Maximilian; Agaimy, Abbas; Zenk, Johannes; Hartmann, Arndt; Iro, Heinrich; Peters, Brigitte; Schwarz, Susanne; Schneider-Stock, Regine (Head and Neck-Journal For the Sciences and Specialties of the Head and Neck, 2014)
The purpose of this study was to determine the prognostic value of O-6-methylguanine-DNA methyltransferase (MGMT) inactivation in a group of 286 patients with salivary gland carcinoma and matched histologically normal tissues.MGMT promoter methylation was studied in 36 patients with salivary gland carcinoma and 19 histologically matched normal tissues by pyrosequencing. MGMT protein expression was examined in 286 patients with salivary gland carcinomas and histologically matched normal tissues by immunohistochemistry on tissue microarrays. The results were correlated to demographic, clinicopathologic parameters, and disease follow-up data.MGMT hypermethylation was significantly (p = .021) associated with the protein loss. MGMT loss was found in 39.2% of salivary gland carcinomas and was predominant in aggressive tumors (poorly differentiated, grade III, regional lymph node involved). MGMT loss significantly (p = .004) predicted poor clinical outcome of salivary gland carcinomas and defined high-risk subgroups in clinically favorable tumor groups.We suggest that immunohistochemical evaluation of nuclear MGMT protein might serve as a tool for the prediction of overall survival in patients with salivary gland carcinoma.
EVALuna2:6616